Subcortical aphasia from a thalamic abscess. Issue 4 (April 1992) - Megens, J; van Loon, J; Goffin, J; Gybels, J
Abstract : A patient is reported who was treated successfully for a left thalamic abscess that resulted in subcortical aphasia. A SPECT scan showed large areas of hypoperfusion in the cortex of the left hemisphere. At follow up after seven months there was marked improvement in the language disorder and the cortical hypoperfusion. It is suggested that aphasia in patients with subcortical lesions results from secondary cortical dysfunctions. The evidence is confined to patients with stroke lesions. The possible implications of this case on current theories of pathophysiological mechanisms, in particular the ischaemic penumbra theory and the cortical diaschisis theory, are briefly discussed. Cortical diaschisis may be the appropriate explanation in this patient.